Evaluation of the effects of red blood cell distribution width on survival in lung cancer patients - Mehmet Kos; Cemil Hocazade; F. Tugba Kos; Dogan Uncu; Esra Karakas; Mutlu Dogan; Hikmet G. Uncu; Nuriye Ozdemir; Nurullah Zengin (Contemporary Oncology)
Aim of the study : Data are available indicating that red blood cell distribution width (RDW) is higher in cancer patients compared to healthy individuals or benign events. In our study, we aimed to investigate the influence of different RDW levels on survival in lung cancer patients. Material and methods: Clinical and laboratory data from 146 patients with lung cancer and 40 healthy subjects were retrospectively studied. RDW was recorded before the application of any treatment. Patients were categorised according to four different RDW cut-off values (median RDW, RDW determined by ROC curve analysis, the upper limit at the automatic blood count device, and RDW cut of value which used in previous studies). Kaplan-Meier survival analysis was used to examine the effect of RDW on survival for each cut-off level. Results : The median age of patients was 56.5 years (range: 26–83 years). The difference in median RDW between patients and the control group was statistically significant (14.0 and 13.8, respectively, p = 0.04). There was no difference with regard to overall survival when patients with RDW ≥ 14.0 were compared to those with RDW < 14.0 (p = 0.70); however, overall survival was 3.0 months shorter in low values of its own group in each of the following cut-off values: ≥ 14.2 (p = 0.34), ≥ 14.5 (p = 0.25), ≥ 15 (p = 0.59), although no results were statistically significant. Discussion : We consider that the difference between low and high RDW values according to certain cut-off values may reflect the statistics of larger studies although there is a statistically negative correlation between RDW level and survival.